fldkkdkdhgg
fldkkdkdhgg
12-06-2020
Mathematics
contestada
f(1) = -3
f(n) = 2 · f(n − 1) +1
f(2)=
Respuesta :
bigbrains123
bigbrains123
12-06-2020
Answer:
-5
Step-by-step explanation:
f(2) = 2 * f(1) + 1
f(2) = 2 * -3 + 1
f(2) = -6 + 1
f(2) = -5
Answer Link
VER TODAS LAS RESPUESTAS ( 96+ )
Otras preguntas
Can you please help me with #32 im getting confused.
how do you explain the midpoint of cd is e (-1,0). one endpoint is c(5,2). what are the coordinates of the other endpoint?
Hello everyone! This is all about simile can you answer this?Instruction: What are compared in the following lines? What do the two unlike objects have in commo
Is 5/8 equivalent to 4/10
What are the zeros of 7x^2 -- 144 = --x^4 please give an explanation and show the work. thank you!
What is the definition of Frame of reference? Is there an equation, if soo what is it?
Robert Hook's discovery helped scientists learn more about _____.
Find the solutions to the given trig equation for 0 < x < 2π: tanx(cosx)=cosx
What is experimental probability?
I need some really interesting facts about Pumice and Sandstone